THE EFFECT OF LIQUIDITY, LEVERAGE, AND SALES GROWTH ON FINANCIAL DISTRESS WITH PROFITABILITY AS MODERATING VARIABLES - Bambang Sugiharto; Trisandi Eka Putri; Risa Masyuniar Nur'alim (JASS (Journal of Accounting for Sustainable Society), 2021)
Financial distress is a condition that occurs when a company's cash flow is disrupted and suffers continuous operational losses which results in the company being unable to pay its obligations or leading to bankruptcy. So the company must know the causes that affect financial distress. Many factors indicate that the company will experience financial distress. This study aims to analyze the factors that affect financial distress with indicators of liquidity, leverage and sales growth and profitability as moderating variables. The results showed that the liquidity ratio calculated by the current ratio had a negative effect on financial distress. Leverage calculated by DAR (debt to asset ratio) has a positive effect on financial distress. Sales Growth which is calculated by current year's sales minus last year's sales and divided by last year's sales has a negative effect on financial distress. In addition, profitability as avariable is moderating only able to moderate the effect of liquidity on financial distress but is not able to moderate the effect of leverage and sales growth on financial distress.